PENGARUH PENDEKATAN SAINTIFIK BERBASIS PENILAIAN KINERJA TERHADAP PENGUASAAN KOMPETENSI PENGETAHUAN IPS DITINJAU DARI KEMAMPUAN BERPIKIR KREATIF - Ayu Wulandari (Journal for Lesson and Learning Studies, 2018)
This study aims to (1) to know the significant difference of cognitive competence control of IPS among students who follow the learning with scientific approach based on performance appraisal and implementation of learning with scientific approach, (2) to know the significant difference of mastery of IPS cognitive competence among students who have ability high creative thinking and low creative thinking ability, (3) to know the interaction of learning implementation with scientific implementation based on performance appraisal and creative thinking ability to master IPS cognitive competence. The design of this research is Nonequivalent Control Group Design, using factorial design 2x2 Anava Dua Lane. Population in this study all students of class V SDN Ir. Soekarno Denpasar Selatan academic year 2015/2016. The data collected are data of creative thinking ability and IPS cognitive competence.          The results of the study showed that (1) there was a significant difference of IPS learning outcomes between students who were educated through a scientific approach based on performance appraisal with groups of students who were taught by conventional scientific approach FAhitung = 4,94> F tabel(α = 0,05; 1,82)= 3,98), (2) there is no significant difference between mastery competence cognitive social class to the ability of creative thinking high and the capacity to think creative low students and the (FB =0,97 > F tabel(α = 0,05; 1,82)) = 3,98) , (3) there are the influence of an interaction between rendering based approach performance assessment and creative thinking learning of the results of the social class (FABhitung = 12,28 > F tabel(α = 0,05; 1,82)= 3,98).Keywords: Performance Appraisal, Creative Thinking, IPS Cognitive Competence